Hematological, biochemical and microbiological evaluation of feline whole blood units collected using an open system and stored for 35 days. (December 2019) - Spada, E.; Perego, R.; Baggiani, L.; Martino, P.A.; Proverbio, D.
Highlights: The effect of storage on selected hematologic and biochemical parameters for feline whole blood units were reported. Statistically significant increases in hemolysis and erythrocyte morphologic change become evident from 21 days storage. Mean percentage hemolysis was <1% up to 21 days of storage. Statistically significant changes in biochemical parameters (glucose, potassium, and sodium) commenced from 7 days storage. In vivo studies are needed to verify the clinical relevance of changes in feline blood during storage. Abstract: Despite the increasing availability of feline blood, which is collected and stored for transfusion purposes, few studies have assessed the effect of storage on feline whole blood (WB) units. The purpose of this study was to investigate selected hematologic and biochemical changes during storage of feline WB units and to determine when they occurred. Data from a quality control program for WB units was used in this study. Twelve feline WB units, collected using an open system, were sampled every 7 days from the point of collection to the end of storage at 35 days (D0, D7, D14, D21, D28, and D35). Measurements at each time point were: (1) hematologic parameters; (2) percentage hemolysis; (3) morphologic index scored at 0–3, based on echinocyte transformation of the erythrocytes; and (4) selected biochemical parameters. Aerobic and anaerobic culture was performed at D0 and D35. Results were compared statistically to D0 (statistical significance set at <0.01). Storage did not result in statistically significant changes in measured hematological parameters. There were statistically significant increases in percentage hemolysis and morphologic index, starting from D21 ( P = 0.000 and P = 0.004, respectively). Glucose decreased significantly from D21 (P = 0.003); potassium increased significantly from D7 (P = 0.001); and sodium increased significantly, starting from D28 ( P = 0.009). Bacteria were not isolated. Blood in feline WB units collected using an open system underwent some significant storage changes that were time-dependent. As these changes could affect the quality and the utility of stored WB used in feline transfusion medicine, further study is required to determine their clinical importance.